Case Study of Optimization of Distribution Costs in the Logistics Supply Chain - Peter MAJERCAK (Communications of International Proceedings, 2021)
Integrating logistics function is well known and appreciated. The importance of logistics is also growing with the development of integrative tendencies when individual regional markets acquire the character of global markets. The possibility of using logistics as an effective tool of a competitive fight by increasing market share is considered as an important factor. Price, quality, advertisement of comparable products do not differ in many ways. The difference possibilities are focused on the field of customer service providing and costs reduction associated with the management and implementation of goods and information flows. Paper shows the importance of logistics optimization in the whole supply chain.
Keywords: Logistics; supply chain; distribution costs; economy